Pengaruh Faktor Budaya, Sosial, Pribadi, Psikologis, Dan Bauran Pemasaran Terhadap Keputusan Pembelian Kebaya Bordir Pada Jegeg Ayu Boutique Di Kuta - Pratiwi, Ketut Indah; Mandala, Kastawan (E-Jurnal Manajemen, 2015)
The purpose of this study was to investigate the influence of cultural, social, personal, psychological, and marketing mix to the purchasing decision kebaya embroidery on Jegeg Ayu Boutique in Kuta. This research was conducted in Jegeg Ayu Boutique Kuta, samples taken were 108 respondents with purposive sampling method. The collection of data by distributing questionnaires using 5-point Likert scale, to measure 18 indicators. The analysis technique used is multiple linear regression analysis. These results indicate that the positive influence of cultural factors on purchasing decisions kebaya embroidery on Jegeg Ayu Boutique in Kuta. Social factors positive influence on purchase decisions kebaya embroidery on Jegeg Ayu Boutique in Kuta. Personal factor positive influence on purchase decisions kebaya embroidery on Jegeg Ayu Boutique in Kuta. Psychological factors have positive influence on purchase decisions kebaya embroidery on Jegeg Ayu Boutique in Kuta. Last, marketing mix positive influence on purchasing decisions kebaya embroidery on Jegeg Ayu Boutique in Kuta .
Keywords: cultural; social; personal; psychological; marketing mix; purchasing decisions